Challenges Evaluation for Adoption of SCP Practices in Footwear Industry of Bangladesh: A DEMATEL Approach. Issue 2 (December 2018) - Ali, Kauser; Moktadir, Md. Abdul; Shaikh, Aftab Ali; Deb, Amal Kanti; Rashed-Ul-Islam, Md.
Abstract: The footwear industry needs a sustainable business environment due to its remarkable contributions to the economic growth of a country. Sustainable consumption and production (SCP) practices in the footwear industry can act as a pivotal driving factor for sustainable development in footwear sector of Bangladesh. The implementation of SCP practices is not an easy task for the footwear industry since there are numerous challenges in the existing supply chain. Meanwhile, the literature reveals that the lack of studies on relevant industry motivates to carry out this research. Therefore, this research focuses on the state-of-the-art literature by identifying and finding interactions among challenges to SCP practices in the footwear supply chain. Five experts from five reputed and export-oriented footwear industries were assigned to find out the challenges regarding the SCP implementation and the most important 10 challenges were identified based on experts' feedback. To assess the cause–effect relationship among challenges, a decision-making trail and evaluation laboratory (DEMATEL) technique, a powerful decision-making tool which can find the interactions among factors, was employed. In this study, results showed that five challenges were identified as causal group challenges and remaining five identified as effect group challenges. The causal challenges are lack of top management commitment, absence of market information of green products, inadequate training facility on SCP, motivational gap among consumers, and lack of rules and regulations on SCP practices. Those challenges have net positive influence on effect group challenges such as poor compliance practices, lack of latest technological facility, lack of acceptance on green products, lack of reverse logistics facility, and poor linkage and coordination among lead firms. These results will assist decision-makers to make strategic policy regarding implementing SCP in the footwear supply chain. This study is the first one which deals with the importance of SCP practices in the context of footwear industry, and it is also important for the sustainable development of footwear sector of Bangladesh.